Lack of association of –863C/A (rs1800630) polymorphism of tumor necrosis factor-α gene with rheumatoid arthritis - Tayyaba Sadaf (Termedia Publishing House, 2019)
Introduction Multifunctional pro-inflammatory cytokine tumor necrosis factor-α (TNF-α) has been implicated in a variety of inflammatory diseases including rheumatoid arthritis (RA). TNF-α polymorphisms are mostly located in its promoter region and play a significant role in disease susceptibility and severity. We therefore sought to investigate TNFA –863C/A (rs1800630) polymorphism association with RA activity in our Pakistani study group.